2014
DOI: 10.4062/biomolther.2014.051
|View full text |Cite
|
Sign up to set email alerts
|

Dioscorea Extract (DA-9801) Modulates Markers of Peripheral Neuropathy in Type 2 Diabetic db/db Mice

Abstract: The purpose of this study was to investigate the therapeutic effects of DA-9801, an optimized extract of Dioscorea species, on diabetic peripheral neuropathy in a type 2 diabetic animal model. In this study, db/db mice were treated with DA-9801 (30 and 100 mg/kg, daily, p.o.) for 12 weeks. DA-9801 reduced the blood glucose levels and increased the withdrawal latencies in hot plate tests. Moreover, it prevented nerve damage based on increased nerve conduction velocity and ultrastructural changes. Decrease of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…However, most of the currently available treatments for diabetic neuropathy only relieve the symptoms (Edwards et al ., ). Drugs commonly used to ameliorate the symptoms, such as gabapentin and α‐lipoic acid, are reported to cause various side effects; thus, the development of safer treatments for diabetic neuropathy is of upmost importance (Moon et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, most of the currently available treatments for diabetic neuropathy only relieve the symptoms (Edwards et al ., ). Drugs commonly used to ameliorate the symptoms, such as gabapentin and α‐lipoic acid, are reported to cause various side effects; thus, the development of safer treatments for diabetic neuropathy is of upmost importance (Moon et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Dioscoreaceae yam tubers are usually edible and are rich in many nutrients. ( 5 , 6 ) Dioscorea japonica is good for nutritional fortification, ( 7 10 ) and it has a gastric mucosal protective effect conferred by glycoproteins and digestive enhancement by glycosidase. Recently, we found that Dioscorea japonica extract (DJE) suppressed the expression of COX-2 and mPGES-1 in human non-small-cell lung carcinoma A549 cells and colon carcinoma Caco-2 cells, thereby inducing apoptosis in such cells.…”
Section: Introductionmentioning
confidence: 99%
“…More studies are needed to ascertain their potentials on the overall quality of life. [20][21][22][23] Generally, natural phyto-chemicals showed to be effective and welltolerated by their in vivo-models of DM. Serious side-effects of these phyto-chemicals did not show as an arising problem.…”
Section: Natural Phytochemicalsmentioning
confidence: 99%